MODERATING ROLE OF GENDER DIVERSITY ON THE RELATIONSHIP BETWEEN PSYCHOLOGICAL TRAITS AND ENTREPRENEURSHIP DEVELOPMENT - Basuki (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
This study has examined the relationship between set of psychological traits on entrepreneurship development in Indonesian graduate students. For the better understanding, moderating effect of gender diversity is also observed between psychological trait-entrepreurnship development relationship. For a sample of 270 students from different universities, our research has conducted descriptive analyses, factor loadings, reliability analyses, and regression method for both direct and indirect relationship between the variables. Descriptive results have suggested the normal trends in the data through mean and standard deviation, whereas reliability analyses through CB alpha is providing the evidence that all items are reasonably loading the single factor. Additionally, confirmatory factor analyses has confirmed the individual significance of each item for psychological traits. Finally, regression findings indicates that there is a direct and positive impact of Mean locus of control, mean tolerance for ambiguity, and mean risk taking propensity on entrepreneurship development among the student community in Indonesia. Additionally, the moderating effect of gender diversity is found between locus of control and entrepreurnship development, and between tolerance for ambiguity and entrepreurnship development among the students. Our study has contributed both in theoretical and empirical literature, covering the title of psychological traits in five different dimensions and entrepreurnship too. However, study is limited in terms of missing with structural equation modelling, large sample size, and analyzing the personality traits on entrepreurnship development among other community members in the same region. Future studies may address these limitations for their contribution too.